The Effect of Ophiocephalus striatus Extract on Quantitative Measurement of Biceps Brachii and Rectus Femoris in Patients with Mechanical Ventilation: A Randomised Control Trial - Hunter Design Nainggolan; Eddy Harijanto; Adhrie Sugiarto; Inge Permadhi; Thariqah Salamah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2020)
Introduction A freshwater fish Ophiocephalus striatus (OS) or known locally to Indonesian as haruan, has potentials to retain musclemass of critically ill patients following its high content of amino acids, fatty acids, minerals, and vitamins. This study was conducted to investigate the effect of OS on quantitative measurements of biceps brachii and rectus femoris in patients with mechanical ventilation. Methods This was a double-blinded randomized controlled trial at tertiary hospital between July- September 2019. The study included patients aged 18-65 years old with mechanical ventilation whereas patients with chronic kidney disease, paraparesis, or neuromuscular disorders were excluded. Forty-two patients were divided into extract group (n=19) who received 15 g of OS extract daily and control group (n=23) who received none. Quantitative measurements of both muscles were determined by measuring cross sectional area (CSA) using ultrasonography by one radiologist. Data were collected at 1st and 7th day, while the intervention was administered in-between. Independent sample T-test, Mann-Whitney test, and multivariate study using general linear model (GLM) were used for statistical analysis. Results The changes of CSA on biceps brachii and rectus femoris muscles from before to after intervention between extract group compared to control group were 5,30 ± 2,41 to 6,09 ± 1,81 vs. 5,16 ± 2,50 to 4,16 ± 1,94 (p=0.002) and 2,45 (1,10 – 5,90) to 3,47 (1,13 – 8,18) vs 3,85 (1,09 – 9,06) to 2,78 (1,06 – 7,27) (p=0.230), respectively. Multivariate analysis showed significant differences between extract and control group for both muscles with p value of <0.001 and 0.001 respectively. Conclusion Supplementation of Ophiocephalus striatus extract was associated with a significant increase of biceps brachii and rectus femoris CSA in patients with mechanical ventilation. Keywords: Ophiocephalus striatus, ultrasonography, cross sectional area, biceps brachii muscle, rectus femoris muscle